Interaction of Chinese institutions with host governments in dam construction: the Bui dam in Ghana - Oliver Hensengerth (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The study analyses the role of Chinese companies and financing institutions and Ghanaian governmental agencies in planning and constructing the Bui Dam. The analysis focuses on the division of responsibilities between Sinohydro and China Exim Bank on the one side and the Ghanaian government on the other side. The findings show that environmental and resettlement planning for Bui was commissioned and financed by the Government of Ghana without Sinohydro's involvement. The obligation of the firm is to abide by the environmental regulations that are monitored by the regulatory authorities. The role of Sinohydro consists in building the dam, maintaining the construction site, contracting workers, and providing for workers' health and safety. The firm has no role in resettlement, which is carried out by the Bui Power Authority. While there is clear evidence that the Bui Power Authority does not follow the recommendations of the Resettlement Planning Framework, Sinohydro appears to abide largely by the conditions set out in the Environmental Impact Assessment study whose implementation is monitored by the Ghanaian Environmental Protection Agency and the Ghanaian Water Resources Commission.
Keywords: 330